Analysis of The Removal and Installation Stages of The RR Trent 700 Engine on an Airbus A330 Aircraft Using The Critical Path Method - Husaini, Fahdli Zulfikar; Mufti Arifin; Muhammad Hadi Widanto (FTK UNSURYA, 2025)
The lifting of the Restriction of Community Activities (PPKM) in January 2023 was the beginning of the aviation industry in Indonesia starting to rise marked by the emergence of new Maintenance Repair and Operations (MRO). Limited hangar space at MRO is a challenge in scheduling aircraft maintenance, setting the order of task cards that have been submitted by the airline and must be done in the maintenance project will be an illustration of how long this project will be done. MP item number 7122410504 contains Detailed Inspection of Aft Engine Mount Fail-Safe link is a maintenance job that can be done after the removal of Engine. The engine removal and installation process often takes more time and effort, potentially causing delays in the overall maintenance time. The purpose of this research is to make efficiency in the removal and installation process of the RR Trent 700 engine using the critical path method. The critical path method in analysing the stages of work in the maintenance process aims to identify and optimise resource allocation, so that maintenance time can be minimised and overall efficiency can be improved. The results showed that the application of the critical path method in the stages of engine removal and installation work resulted in a time efficiency of about 1,655 Hours so that the delay in work on the critical path became the main factor affecting the total duration of the engine removal and installation process.